2012
DOI: 10.1007/s00267-012-9877-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Habitat Complexity on Richness, Abundance and Distributional Pattern of Forest Birds

Abstract: Structurally complex forests provide more diverse conditions in comparison to homogenous forests because of greater variety of microhabitats and trees. This study assesses the association of bird species richness, abundance, and distributional pattern with habitat complexity (HC) in Kheyrud Forest in the north of Iran. Birds were surveyed during spring 2009 by 100 point counts. In each point count six habitat features related to the index of HC were computed and scored from 0 to 3. Then the scores were summed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In addition, the diameter at breast height and height of snags determine which species will use the snag for nesting (Thomas et al 1979). Ghadiri Khanaposhtani et al (2012) underlined that high volumes of coarse woody debris, especially large snags, and dense canopy cover are habitat requirements of the black woodpecker, Dryocopus martius, in Hyrcanian Forests.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diameter at breast height and height of snags determine which species will use the snag for nesting (Thomas et al 1979). Ghadiri Khanaposhtani et al (2012) underlined that high volumes of coarse woody debris, especially large snags, and dense canopy cover are habitat requirements of the black woodpecker, Dryocopus martius, in Hyrcanian Forests.…”
Section: Discussionmentioning
confidence: 99%
“…They related this evidence to the increasing colonization probability, greater numbers of resources and more stable microclimatic conditions. Large snags and dense canopy cover are habitat conditions for the black woodpecker, Dryocopus martius, in the Hyrcanian Forests [87]. A low richness of epixylic bryophytes was attributed to a low supply of deadwood in large diameter classes [88].…”
Section: Diameter Of Cwdmentioning
confidence: 99%
“…In general, large snags (size class > 75 cm) represent the most important cavity source for nesting birds, and are more ecologically meaningful than small snags as they can be used by a wider variety of species. For example, in the Hyrcanian forests Ghadiri Khanaposhtani et al (2012) found that high volumes of coarse woody debris (especially large snags) and dense canopy cover are suitable habitat features for the black woodpecker, Dryocopus martius. Similarly, the American marten in the north-eastern US prefers forests with larger downed logs (large-end diameter 21 ± 0.8 cm) and snag volumes of more than 10 m 3 ha -1 (Payer & Harrison 2003).…”
Section: Size Class Distribution Of Snags and Logsmentioning
confidence: 99%